Pentingnya Budgeting dan Menabung Bagi Generasi Muda - Desy Arigawati; Karpi andriyansah; Cahyadi Yusuf Hidayat; Rohana Manullang; Inddah Wulandari Anggreini; Marieta Soehaoni Halawa; Alfian Dewangga Purba; Tabah Siregar; Rachel Octavia (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The Community Service carried out at this school aims to provide a direct contribution to the quality of education and skill development for students and teachers in the school environment. This activity is focused on empowering and increasing the competence of students and teaching staff in facing educational challenges in the modern era. The methods used include education, sharing sessions and mentoring based on real needs in the field .This service activity is carried out with the aim of increasing the quality of the learning process through the application of methods that are more effective and enjoyable for students. It is hoped that, through this activity, a more inclusive and innovative educational environment can be created, which in turn will have a positive impact on the quality of education in schools and encourage active community participation in supporting educational progress in the area.